Correlation of The Implementation of The Scientific Approach with Critical Thinking and Problem Solving Skills of Students on Benzene Material - Destri Endang Lestari; Zonalia Fitriza (Journal of Educational Sciences, 2022)
The 2013 curriculum demands the use of a scientific approach in the learning process. Based on the questionnaire distributed to 10 chemistry teachers in Padang City, it was found that the scientific approach had not been implemented, and students' critical thinking and problem solving skills were still low. The purpose of this research is to describe the correlation of scientific approach with critical thinking and problem solving skills. This type of research is descriptive research with simple random sampling technique. The study was conducted on 33 students in one high school in Padang City. The instruments used are document analysis sheets to see the completeness of teacher documents, observation sheets to see the implementation of the scientific approach, Structured Essay Diagnostic Test of Chemistry (SEDToC) to measure students' critical thinking and problem solving skills on benzene material. The results of the study indicate that the planning prepared by the teacher through the lesson plans has been implemented, but the implementation has not been carried out according to the scientific approach. After learning with a scientific approach, the SEDToC instrument was then given to measure students' critical thinking and problem solving skills. As many as 69% of students are classified as uncritical, 13% are quite critical, 18 are less critical and no students are classified as critical. While the problem solving ability of students is 100% low. The correlation test shows that the implementation of the scientific approach has a positive correlation with students' critical thinking and problem solving abilities.